Dampak Pengembangan Objek Wisata Danau Kelimutu Terhadap Kondisi Ekonomi Masyarakat Sekitar: Studi Pada Masyarakat Desa Ko’anara Kecamatan Kelimutu Kabupaten Ende - Sayful Amrin; Mansur R Hasan (Program Studi Pendidikan Ekonomi, Universitas Flores, 2020)
The research objective was to determine the development of the kelimutu lake tourism object and its impact on the economic situation of the surrounding community. This type of qualitative research with data collection techniques using observation, interviews and documentation. The collected data were analyzed using qualitative descriptive analysis by Miles and Huberman. This research shows (1) The development of the Kelimutu Lake Tourism Object carried out by the Kelimutu National Park Office has been well supported by the availability of facilities and infrastructure, improving the quality of human resourches through training, collaborating with related parties and aggressively carrying out promotional efforts. (2) The existence of the Kelimutu Lake Tourism Object has a positive infuluences on the economic conditions of the Ko’anara Village community. It is proven that there is an increase in the income of people engaged in the tourism sector, as well as the absorption of labour from local communities.